Perilaku Sticky Cost Terhadap Beban Usaha pada Aktivitas Penjualan Kue Karawo di UMKM Li Maya Gorontalo - Valentina Monoarfa; Indah Safitri; Cindi Setiawati (ManBiz: Journal of Management and Business, 2024)
Sticky costs refer to the phenomenon where business expenses do not decrease proportionally with a decline in sales volume but tend to rise more quickly as sales volume increases. This research aims to analyze the behavior of sticky costs on operating expenses in the cake sales activities of the Li Maya SME in Gorontalo. The research methodology involves analyzing the financial data of the Li Maya SME, conducting interviews, and direct observation of operational activities. The results show that some cost components, such as permanent employee salaries, exhibit sticky characteristics, meaning they do not decrease significantly when sales decline. Conversely, these costs increase as sales activity rises.